Peningkatan Kemampuan Komunikasi Dan Pemahaman Konsep Melalui Pendekatan Pembelajaran Metakoqnitif (PTK Pada Siswa Kelas Viia Semester Genap SMP N 1 Ngemplak 2015/2016) - Kristiana, Dini; , Rita P. Khotimah, S. Si., M. Sc (2016)
This study aims to increase the ability of communication and understanding of math concepts students of class VII A SMP Negeri 1 Ngemplak year 2015/2016 through Metakoqnitif learning approach. This research is a class act. The technique of collecting data through observation, testing, field notes, and documentation. The results showed an increase in communication skills students seen from: 1) express mathematical ideas through word of mouth as much as 5 students (15.15%) after the second cycle of 25 students (75.75%), 2) write down the mathematical idea of 4 students (12.12 %) after the second cycle is 20 students (60.6%), 3) explain mathematical concepts as 7 students (21.21%) after the second cycle as many as 15 students (45.45%), and understanding of concepts students seen from: 1) to restate a concept as much as 6 students (18.18%) after the second cycle as many as 18 students (54.54%), 2) classify objects according to certain properties accordance with the concept as much as 6 students (18.18%) after the second cycle is 20 students (60.6%), 3) provide examples and non-examples of the concept as 5 students (15.15%), after the second cycle is 20 students (60.6%). Based on the above concluded that Metakoqnitif learning approach can improve communication skills and understanding of mathematical concepts.